(untitled) (Global Journal of Human-Social Science, 2022)
From a critique of journalistic practice this article works on the hypothesis that the work of Honor de Balzac approaches a literature of complexity through the engendering of a network of characters knowledge plots and actions Through primary and secondary literature review we observed that Balzac recovers the etymological meaning of the word complexus what weaves together MORIN 1996 In our view Balzac adopts a recursive hologrammatic and knowledge reconnection methodology Our analysis identifies communicational aesthetic and literary aspects in the French author and classifies him as a transdisciplinary artist- researcher of diffuse poetic interest and endowed with immense imagination Our conclusion suggests the need for further research between the communicational literary and complexity fields